(3OdGdI GdHQgGf defUaj GdENhGf Ydi WQjb GdEjeGfs - (3GdHbGYj , EHQGgje Hf YeQ Hf MSf GdQHGW Hf Ydj Hf CHj HcQ GdHbGYj GdTGaYj, HQgGf GdOjf CHh GdMSf,J (B885 (3g` s ((3OeTb s)
(3ChdgG (B:s
(3hHYO agPg EfgGA GdNdGa cJGH SGdfi ajg HYV GdGNhGf SejJg OdGdI GdHQgGf Ydi Cf ai GdGecGf GHOY eeG cGf dCf QHfG GdQMef cd jhe gh ai TCf s
(3BNQgG (B:s
(3Cf jWdb gPg GdYHGQI GdXGgQI ai GdfbU eUGOeJgG dUQGFM ef cdGeg aGSJZP HGddg efTQ GdfaS hGdghi hQGb Gdedc GdGYdi gPG BNQ eG GQOJ EKHGJg ef OdGdI GdHQgGf Ydi Gf ai GdGecGf GHOY eeG cGf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ ai MjGI GdeDda s
(3HCKfGA GdfSNI EdMGbGJ dYdgG HNW GdeDda s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B56 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B71s
Keywords: (3GdJhMjO hGdedd hGdfMds